Three Ways Aliphatic Aldehydes React with Nonstabilized Azomethine Ylides - Gorbunova, Evgeniya V.; Buev, Evgeny M.; Moshkin, Vladimir S.; Sosnovskikh, Vyacheslav Y. (Synlett, 2020)
Aliphatic aldehydes readily react with nonstabilized azomethine ylides in one of the three ways to give oxazolidines, pyrrolidines, or Mannich bases, depending on the structure of the starting compound and the reaction conditions. The use of N-(methoxymethyl)-N-[(trimethylsilyl)methyl]benzylamine in DMF provided 5-alkyloxazolidines in 40–97% yields. On the other hand, three-component reactions of aliphatic aldehydes bearing one α-hydrogen with N-methyl(benzyl)glycine and formaldehyde gives Mannich bases in yields of 47–98%. A similar reaction of aldehydes bearing branched alkyl groups and two hydrogen atoms at the α-position proceeds as a domino process that gives 3-alkyl-3-formylpyrrolidines in yields of 34–93%.
Keywords: aldehydes; azomethine ylides; oxazolidines; pyrrolidines; Mannich bases